Thermal Analysis of Direct Liquid-Immersed Solar Receiver for High Concentrating Photovoltaic System - Xinyue Han; Qian Wang; Jun Zheng; Jian Qu (International Journal of Photoenergy)
Concentrator solar cells that operate at high solar concentration level must be cooled. In this paper, direct liquid immersion cooling of triple-junction solar cells (InGaP/InGaAs/Ge) is proposed as a heat dissipation solution for dense-array high concentrating photovoltaic (HCPV) systems. The advantages of triple-junction CPV cells immersed in a circulating dielectric liquid and dish HCPV technology are integrated into a CPV system to improve the system electrical conversion efficiency. An analytical model for the direct liquid-immersed solar receiver with triple-junction CPV cells is presented. The main outputs of the model are the components temperatures of the receiver and the system electrical efficiency. The influence of concentration factor, mass flow rate, and inlet liquid temperature on the operating temperature of the triple-junction CPV cells and the system electrical conversion efficiency are discussed. It is shown that the system electrical conversion efficiency is very high for a wide range of operating conditions. The three operating parameters have a major effect on the operating temperature of the triple-junction CPV cells and, by extension, system output power. The flow rate selection should match concentration factor to keep the triple-junction CPV cells temperature lower and increase the electrical conversion efficiency of the dense-array HCPV system.